Pengaruh Rasio Profitabilitas dan Likuiditas terhadap Return Saham dengan Inflasi sebagai Variabel Moderasi - Naurah Aurellia Widya Putri (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study intends to study the influence of profitability and liquidity ratio well-being on stock return with inflation as the moderate variable. This research uses a type of causality research that uses quantitative. This research uses purposive sampling of 63 companies in BEI's essential and chemicals industry for 3 years (2018-2020). The statistical analysis in this research is used the SPSS version 26. The study used an analytical tool called Moderate Regression Analysis (MRA). The results of this research showed that return on assets was a significant positive effect on stock return. The current ratio has no significant impact on stock return because the number of existing assets is too high, and they couldn't take advantage of it as much as possible. The rate of inflation in the testing of this couldn't be proved to be a moderating variable and able to strengthen the effect of ROA and CR on the essential and chemicals industry, because the drop rate of inflation in this research period is relatively light so, doesn't have much impact of ROA and CR on stock return.